Making a good death: AIDS and social belonging in an independent church in Gabarone - Klaits, F. (My University, 1998)
In September 1997, the Botswana Government sponsored the second annual Month of Prayer intended to involve churches in HIV/AIDS education and prevention efforts. At the opening ceremony for this Month of Prayer, B.K. Sebele, the Permanent Secretary in the Ministry of Labour and Home Affairs, announced that about 148,000 HIV infections had occurred in Botswana between 1992 and 1997, and that 25% of the national population between ages 14 and 49 were currently estimated to be HIV-positive. He went on to remark that churches have an important role to play in setting an example of sexual morality. Sebele argued that by advocating faithfulness in marriage, church leaders might succeed in inducing people to change their sexual behavior. Government and churches have, however, multiple and potentially conflicting agendas in AIDS prevention efforts, as has become apparent, for instance, in tensions over the advocacy of condom use. In this paper I take a somewhat different perspective on such multiple agendas. Rather than focusing on what religious leaders tell their followers about marriage and sexual morality, or how church participants understand sexual commitment, I concentrate on how members of a particular independent church in Old Naledi, a former squatter community in Gaborone, come to terms with one another's illness and death. Over the past two years, the Utlwang Lefoko (Hear the Word) Apostolic Church has lost three of its members, including the husband of the founding Bishop, as well as numerous close relatives who had not attended their church. In this context, the primary anxiety of many church members is how to transform experiences of illness and death into affirmations of their faith and of their social belonging. This concern is not necessarily the same as those of public health officials and AIDS educators, and it is important to appreciate its legitimacy. In order to illustrate this issue, I present here a case study of an illness and death of a woman member of Hear the Word, who passed away in May 1997 at age 22. I have been involved in this church since 1993, when I began to develop a student-teacher and disciple-minister relationship with the Bishop.
African Studies Seminar series. Paper presented 16 March 1998
Keywords: AIDS (Disease). Botswana. Gabarone; AIDS (Disease). Religious aspects. Christianity; Social acceptance; Utlwang Lefoko Apostolic Church